Costs Optimization for Unit Commitment and Economic Load Dispatch in Large Scale Power Systems - Norhamimi, .; Musse, Mohamud Ahmed; Ismail, Hassan (2004)
Power generation business profit depends on the power systems operational costs. Finding an optimal solution to the unit commitment (UC) and economic load dispatch (ELD) is one of the smart strategies that being practiced by most of power producers. UC and ELD main problems are to find the minimum total fuel cost and fast computation simulation time scheduling of UC and ELD. Obtaining the best solution to these two problems lead to remarkable saving in the power system operational cost Lagrangian relaxation (LR) is one of the best solution methods to UC and ELD problems. The approach is more efficient and easier than other methods in solving large-scale problems. Lately, the emerging of bundling methods (BM) improves the weakness of LR. Through BM, the LR dual functions are updated at the higher level. With the use of interior point method as an initialization method this paper presents LR and BM based solution technique to UC and ELD problems. It is based on application of the said techniques to thermal units consisting of 45 generators. A comparison has been made with a data taken from Tenaga Nasional Berhad (TNB) and the results found from this system have been compared to that of TNB results.